Strengthening Youth Entrepreneurial Orientation among Vocational School Students in Yogyakarta Province (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community engagement program aimed to strengthen Entrepreneurial Orientation (EO) among vocational school (SMK) students in Yogyakarta Province through an EO-based entrepreneurship training. Using a one-group pre-test–post-test design, the program was delivered on July 17, 2025, at Rumah BUMN Sleman to 40 participants recruited via an open call in collaboration with the DI Yogyakarta Education and Sports Department. Training covered (1) business idea and plan development (Business Model Canvas), (2) basic financial literacy, and (3) digital marketing and market analysis (TikTok-based campaigns). Descriptive evaluation shows substantial improvements across four domains: Business Understanding (mean 1.72→4.17; +142%), Financial Literacy (1.60→4.21; +163%), Marketing Analysis (1.57→4.13; +163%), and Entrepreneurial Orientation (1.58→4.43; +180%). These findings suggest that EO-informed participatory training can rapidly improve entrepreneurial readiness among youth; however, continued mentoring is recommended to translate short-term learning gains into sustained business performance.